2019
DOI: 10.1111/srt.12751
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of steatocystoma multiplex and hidradenitis suppurativa: Assessment of this unique association by means of ultrasonography and Color Doppler

Abstract: Background Steatocystoma multiplex (SM) is an uncommon skin disease manifesting as multiple sebum‐containing cysts arising in pilosebaceous unit‐rich body areas. Hidradenitis suppurativa (HS) is a debilitating chronic inflammatory disease affecting the apocrine gland‐bearing skin and presenting with both pseudocystic and inflammatory nodules, abscesses and fistulas. Considering that genetics has been reported to play a role in both entities, the albeit rare association between them suggests a shared genetic ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…These included a widening of the regional hair follicles, decreased dermal echogenicity, dermal and subcutaneous pseudocysts, fluid collections, and fistulous tracts in the intertriginous regions . The association of SCM and HS has been previously described in the literature . Hollmig and Menter reported a case of SCM and HS in the context of a family association.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These included a widening of the regional hair follicles, decreased dermal echogenicity, dermal and subcutaneous pseudocysts, fluid collections, and fistulous tracts in the intertriginous regions . The association of SCM and HS has been previously described in the literature . Hollmig and Menter reported a case of SCM and HS in the context of a family association.…”
Section: Discussionmentioning
confidence: 85%
“…[18][19][20][21] The association of SCM and HS has been previously described in the literature. [22][23][24] Hollmig and Menter 22 reported a case of SCM and HS in the context of a family association.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 The overlap of these 2 conditions could be suggestive of an unrecognized common defect in follicular proliferation. Mutations in keratin 17 (KRT17), a gene encoding the type 1 intermediate filament chain keratin 17 found in sebaceous glands, hair follicles, and other epidermal appendages, have been identified in patients with SM as well as patients with paronychia congenita type 2 (PC-2) 5,14 PC2 is an autosomal dominant disorder associated with nail dystrophy, palmoplantar keratoderma, follicular keratosis, and epidermal inclusion cysts. 4 The presence of the KRT17 mutation in both of these clinical entities is suggestive of different phenotypic expressions.…”
Section: Discussionmentioning
confidence: 99%
“…18 Ultrasonography with color doppler has also previously been reported as a non-invasive tool to help differentiate HS and SM. 5 Management strategies for SM and SMS include local destructive methods (cryotherapy, CO2 and Erbium YAG), oral medications (antibiotics, isotretinoin), and surgery of symptomatic lesions. 4,7,8 Isotretinoin was commonly used in the literature for SMS, helping to control the size of suppurative lesions, likely due to its anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…M = muscles, SF = subcutaneous fat J Korean Soc Radiol selection bias in the inclusion of patients for our study, as typical multiple intradermal steatocystomas were not referred for ultrasound examination. A recent report by Zussino et al(11) showed that steatocystomas may appear as hypoechoic nodules with well-defined hyperechoic borders with absence of Color Doppler signal. Furthermore, posterior acoustic enhancement could be seen when the internal content was liquid.…”
mentioning
confidence: 99%